PENGARUH PENGGUNAAN TEKNIK VISUALISASI TERHADAP PENINGKATAN PERSEPSI IBU TENTANG PEMENUHAN GIZI ANAK DALAM PENCEGAHAN STUNTING - Hilda Yani Karo-Karo; Purnama Sari Cane (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2026)
Background: Stunting remains a major public health problem in low- and middle-income countries, including Indonesia, where maternal age, education, knowledge, and perception play pivotal roles in child nutrition and growth outcomes. Objective: This study aimed to assess maternal characteristics, knowledge, and perceptions related to breastfeeding and nutrition, and to evaluate the effect of visualization techniques on improving maternal perception of child nutrition in the prevention of stunting. Methods: A cross-sectional design was applied involving 100 mothers as respondents. Data were collected on maternal age, education, employment status, knowledge of breastfeeding and stunting, and perception of child nutrition. An intervention using visualization techniques was conducted, and its effect on maternal perception was analyzed using chi-square tests and risk estimates with 95% confidence intervals. Results: Nearly half of the respondents were adolescent mothers (<18 years, 48%), while 45% had only basic education. A majority of mothers demonstrated good knowledge about breastfeeding and stunting (68%) and positive perceptions of nutrition (65%). However, knowledge and perception gaps remained among those with lower education. The use of visualization techniques significantly improved maternal perception of nutrition (p = 0.003), with mothers in the intervention group being four times more likely to report good perception compared to controls (OR = 4.0; 95% CI: 1.647–9.715). Conclusion: Maternal characteristics, particularly young age and low educational attainment, remain challenges for effective stunting prevention. Visualization-based education is an effective strategy to improve maternal perception and should be integrated into community health programs. Strengthening maternal nutrition literacy through innovative, accessible, and interactive interventions is essential to reduce stunting prevalence.